Antidepressant Advisor (ADeSS): a decision support system for antidepressant treatment for depression in UK primary care – a feasibility study. Issue 3 (3rd March 2023) - Harrison, Phillippa; Carr, Ewan; Goldsmith, Kimberley; Young, Allan; Ashworth, Mark; Fennema, Diede; Duan, Suqian; Barrett, Barbara M; Zahn, Roland
Abstract : Objectives: To develop and probe the first computerised decision-support tool to provide antidepressant treatment guidance to general practitioners (GPs) in UK primary care. Design: A parallel group, cluster-randomised controlled feasibility trial, where individual participants were blind to treatment allocation. Setting: South London NHS GP practices. Participants: Ten practices and eighteen patients with treatment-resistant current major depressive disorder. Interventions: Practices were randomised to two treatment arms: (a) treatment-as-usual, (b) computerised decision support tool. Results: Ten GP practices participated in the trial, which was within our target range (8–20). However, practice and patient recruitment were slower than anticipated and only 18 of 86 intended patients were recruited. This was due to fewer than expected patients being eligible for the study, as well as disruption resulting from the COVID-19 pandemic. Only one patient was lost to follow-up. There were no serious or medically important adverse events during the trial. GPs in the decision tool arm indicated moderate support for the tool. A minority of patients fully engaged with the mobile app-based tracking of symptoms, medication adherence and side effects. Conclusions: Overall, feasibility was not shown in the current study and the following modifications would be needed to attempt to overcome the limitations found: (a) inclusion of patients who have only tried one Selective Serotonin Reuptake Inhibitor, rather than two, to improve recruitment and pragmatic relevance of the study; (b) approaching community pharmacists to implement tool recommendations rather than GPs; (c) further funding to directly interface between the decision support tool and self-reported symptom app; (d) increasing the geographic reach by not requiring detailed diagnostic assessments and replacing this with supported remote self-report. Trial registration number: NCT03628027 .